Teprotumumab and Hearing Loss: Case Series and Proposal for Audiologic Monitoring - Belinsky, Irina; Creighton, Jr, Francis X; Mahoney, Nicholas; Petris, Carisa K; Callahan, Alison B; Campbell, Ashley A; Kazim, Michael; Lee, H B Harold; Yoon, Michael K; Dagi Glass, Lora R (Ophthalmic plastic and reconstructive surgery, 2022)
To present a protocol for audiologic monitoring in the setting of teprotumumab treatment of thyroid eye disease, motivated by 4 cases of significant hearing loss, and review the relevant literature. Cases of hearing loss in the setting of teprotumumab were retrospectively elicited as part of a multi-institutional focus group, including oculoplastic surgeons, a neurotologist and an endocrinologist. A literature review was performed. An aggregate of 4 cases of teprotumumab-associated hearing loss documented by formal audiologic testing were identified among 3 clinicians who had treated 28 patients. Teprotumumab may cause a spectrum of potentially irreversible hearing loss ranging from mild to severe, likely resulting from the inhibition of the insulin-like growth factor-1 and the insulin-like growth factor-1 receptor pathway. Due to the novelty of teprotumumab and the lack of a comprehensive understanding of its effect on hearing, the authors endorse prospective investigations of hearing loss in the setting of teprotumumab treatment. Until the results of such studies are available, the authors think it prudent to adopt a surveillance protocol to include an audiogram and tympanometry before, during and after infusion, and when prompted by new symptoms of hearing dysfunction.